Design and Experimental Study of a Modified Cyclonic Microbubble Flotation Column System. Issue 3 (3rd March 2020) - Li, Yanfeng; Pan, Hao; Li, Ningbo; Jiang, Wenlong; Li, Yi; Zhang, Wenjun; Peng, Zhengbiao
ABSTRACT: The cyclonic–static microbubble flotation column (FCSMC) has been proven to be a promising technique for recovering fine-grained minerals. However, low recovery of coarse coal particles by the FCSMC has been reported due to utilization of a single mineralization step. In the present study, a novel modified flotation unit has been added to the conventional FCSMC to improve the recovery of coarse coal particles. The design aspects and operating procedures of the proposed modified cyclonic microbubble flotation column (MCMFC) were studied and the results were compared with the conventional FCSMC. Some data on the applications of MCMFC in industrial floatation processes have also been discussed. The results showed that MCMFC provided higher recovery of coarse coal particles compared to those by FCSMC. Specifically, for −500 + 250 μm coarse particles, the yield by MCMFC was 22.29% higher than that by FCSMC. Both concentrate yield and concentrate ash were found to be significantly affected by the inclusion of the modified flotation unit.